2003
DOI: 10.1002/j.1839-4655.2003.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship — False Premises and Dangerous Forebodings

Abstract: As a reaction against neo‐liberalism, Social Entrepreneurship has been promoted as the solution to welfare problems brought about by social change and persistent unemployment. The Social Entrepreneurship Movement (SEM) proposes the reconstruction of welfare by building social partnerships between the public, social and business sectors. Major aspects of this agenda include non‐profit organisations undertaking entrepreneurial ventures and the pooling of government welfare funding under the control of local comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 5 publications
1
36
0
4
Order By: Relevance
“…The study of SE under a business lens demonstrated how academics and practitioners are adding more effort to investigate the enterprise side of SE, and leaving the social aspect to be studied to a minor degree by other schools. This concurred with Cook et al (2003), who distinguished that SEship literature has less emphasis on the social and more on the entrepreneurial activities and abilities of individuals. Other disciplines, such as, economics, education, and social science, although they have a close relationship with management and business categories, presented papers with the evident intention of exploring the other side of SE, that is its social implication.…”
Section: Se and Seship Research And Theorysupporting
confidence: 69%
“…The study of SE under a business lens demonstrated how academics and practitioners are adding more effort to investigate the enterprise side of SE, and leaving the social aspect to be studied to a minor degree by other schools. This concurred with Cook et al (2003), who distinguished that SEship literature has less emphasis on the social and more on the entrepreneurial activities and abilities of individuals. Other disciplines, such as, economics, education, and social science, although they have a close relationship with management and business categories, presented papers with the evident intention of exploring the other side of SE, that is its social implication.…”
Section: Se and Seship Research And Theorysupporting
confidence: 69%
“…This insight is reflected in the social entrepreneurship paradigm. The literature on social entrepreneurship mirrors this perception as researchers conceptualize social entrepreneurship in a variety of contexts (Alvord, Brown, & Letts, 2004;Dees, 1998;Thompson, Alvy, & Lees, 2000;Witt, 2007), including non-governmental not-for-profit organizations (Weerawardena & Mort, 2006), for-profit activities within social organization that support social causes (Cook, Dodds, & Mitchell, 2003;Wallace, 1999), and innovative actions within for-profit organizations that promote social causes (Thompson et al, 2000). Greenberger and Sexton (1988), in their model of venture initiation, argue that EV is related to the underlying cause or type of venture.…”
Section: The Content Of Entrepreneurial Visionmentioning
confidence: 96%
“…Whether they establish profit or non-profit businesses, social entrepreneurs are willing to forgo profits and growth for a higher social value . As stated earlier, the intent of social entrepreneurship is to enhance society; however, Cook et al (2003) argue that the Social Entrepreneurship Movement (SEM) is based on two major false premises and also has some alarming implications with regard to unemployment and welfare. They believe that proposals established through the SEM do not provide solutions to unemployment or welfare but instead threaten potential solutions posed by other entities.…”
Section: Adopting a Mission To Create And Sustain Social Value (Not Jmentioning
confidence: 99%